Fabrication of antibacterial bio composite from bacterial cellulose and Areca Catechu extract - Khalilurrahman, Azizan (2012)
Wound can be defined as any physical injury involving a break in the skin that usually caused by an act or accident rather than by a disease. The poor healing wound may slow down the healing process thus will be exposed to the infection of bacteria. To prevent the infection to do not further develop, it is important that the wounds be treated earlier. Therefore, the objective in this study was to produce antibacterial bio composite from bacterial cellulose (BC), starch, glycerol and areca nut extract. This bio composite, besides having the antibacterial properties that are needed for wound healing process, it also possess biodegradable capability. The 25 types of bio composite were fabricated from difference composition of bacterial cellulose (0 wt. %, 7 wt. %, 14 wt. %, 21 wt. % and 28 wt. %) and areca nut extract (0%, 25%, 50%, 75% and 100%).These films will be characterized by using phenolic content test, testing for antibacterial activity, biodegradation by using fungus, soil degradable test, water absorption test, quantitative of tannin test, Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM).The antibacterial bio composite showed the presence of phenol and tannin compound by the phenolic content and quantitative of tannin test. The bio composite film that had 100% areca nut extract displayed better antibacterial properties for antimicrobial test against E. coli and S. aureus. The composite shows the degradable characteristic by the soil degradable test and test of biodegradable by incubate the film with Aspergillus niger strain due to the decrease of bio composite weight. For the water absorption test, the highest percentage of areca nut extract and lowest percentage of bacterial cellulose showed the optimum water uptake. From the FTIR test, the bio composite showed the presence of a carbonyl group, hydroxyl group and carbon-oxygen (C-O) bond. An addition, Scanning Electron Microscopy (SEM) was used to observe surface and cross section of the bio composite films. In order to improve the production of antibacterial film, more study should be done to investigate the effect when the film expose to the environment conditions. The fresh areca nut should be used to make sure the phenolic content in the areca nut do not degrade or decrease. Some improvement can be done by study the most suitable solvent that can be used to improve the extraction process. The combination of bacterial cellulose (BC), starch and areca nut extract can be used to produce antibacterial bio composite films which give benefit for wound healing process.